Mobile Application for Energy Efficiency Management in Manufacturing - León-Trejo, Luis; Cabanillas-Carbonell, Michael (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Energy efficiency in industrial sectors consumes 40% of global energy and generates more than 30% of greenhouse gas emissions, contributing to air pollution that affects more than 90% of the world’s population. The research focused on developing a mobile application for energy efficiency management in manufacturing companies. Using the Mobile D methodology, recognized for its effectiveness in project management and its focus on test-driven development, continuous integration, and optimization of software processes, a prototype application was created. This prototype was evaluated by former experts and company staff, such as managers and supervisors, who rated its usability, design, security, efficiency, effectiveness, and functionality with high scores, ranging from 4.58 to 4.91 on a Likert scale. The mobile application includes functions such as equipment registration, allowing users to enter devices and their energy consumption; real-time monitoring and control with alerts if any machine exceeds its normal consumption; and detailed visualizations of energy efficiency, with monthly, quarterly, or annual analysis according to the corresponding areas.